Masa Depan Industri Pariwisata Kota Palangka Raya (Perspektif dan Solusinya) - Trecy E. Anden (LPPM Universitas Palangka Raya, 2021)
The tourism industry is a driver of the economy nationally, regionally and locally. As one source of local revenue (PAD) city of Palangka Raya, this sector received priority attention. Since the last 10 years developing the tourism industry and has developed a fairly good growth. This sector could boost GDP growth in the field of business; perdagangangn. hotels and restaurants. But seen from the growth in tourist arrivals is still dominated by local tourist arrivals, tourist arrivals have not been well explored. Some of the problems, challenges and constraints experienced in the development of the tourism industry. This condition is a manifestation of improvement and even become a dilemma that must be managed in harmony. The future of the city of Palangka Raya tourism industry has good prospects can be anticipated by considering the factors that influence. The study was conducted in the districts that have the potential of nature tourism (ecotourism), using descriptive qualitative research methods and kunatitif and SWOT analisis. In terms of the economy, the tourism sector of the city of Palangka Raya has particularly bright future . The growth rate of GDP, trade, hotel and restaurant sector the role of tourism as a revenue contributor serial number 3.